2011
DOI: 10.5194/bg-8-3747-2011
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical controls on the bacterial populations in the eastern Atlantic Ocean

Abstract: Abstract.Little is known about bacterial dynamics in the oligotrophic ocean, particularly about cultivable bacteria. We examined the abundance of total and cultivable bacteria in relation to changes in biogeochemical conditions in the eastern Atlantic Ocean with special regard to Vibrio spp., a group of bacteria that can cause diseases in human and aquatic organisms. Surface, deep water and plankton (<20 µm, 20-55 µm and >55 µm) samples were collected between 50 • N and 24 • S. Chlorophyll-a was very low (<0.3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 65 publications
4
28
0
Order By: Relevance
“…The empirical formula for Vibrio spp. derived here shows a temperature effect that is the same as was derived for the Atlantic Ocean by Neogi et al . Other formulas from the literature (Table ) did not show any correspondence.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The empirical formula for Vibrio spp. derived here shows a temperature effect that is the same as was derived for the Atlantic Ocean by Neogi et al . Other formulas from the literature (Table ) did not show any correspondence.…”
Section: Discussionsupporting
confidence: 85%
“…As reviewed previously, quantitative predictions on future Vibrio concentrations in recreational waters are lacking . In the literature, several empirical relations between Vibrio presence or concentration and environmental factors have been described . Table gives an overview of empirical relations between the concentration of Vibrio spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, elucidating the relationships between DOC dynamics and BA is a significant ecological issue. Temperature is among the most important ecological parameters affecting phytoplankton composition, bacterial growth, and biological activity (White et al 1991;Kobari et al 2010;Neogi et al 2011). Bacterial abundances in our study were within the range reported by Zhu et al (2009) in their study of Lake Taihu.…”
supporting
confidence: 88%
“…Previous studies have reported that BA is controlled by DOC concentration (Naganuma & Seki 1993;Neogi et al 2011) and that bacteria can rapidly utilize DOC of autochthonous origin (Chen & Wangersky 1996). However, the interaction between DOC and BA is complex, as the interaction can be affected by other factors, such as photodegradation of DOC (Lindell et al 1995;Catal an et al 2013) and bacteria loss due to sedimentation and grazing (Work & Havens 2003;Tang et al 2010).…”
mentioning
confidence: 99%